Adsorption of acid orange 7 by cetylpyridinium bromide modified sugarcane bagasse - Nik Malek, Nik Ahmad Nizam (Penerbit UTM Press, 2016)
In the present study, the adsorption of acid orange 7 (AO7) dye from aqueous solution by sugarcane bagasse (SB) and cetylpyridinium bromide (CPBr) modified sugarcane bagasse (SBC) was examined. SBC was prepared by reacting SB with different concentrations (0.1, 1.0 and 4.0 mM) of cationic surfactant, CPBr. The SB and SBC were characterized using Fourier transform infrared (FTIR) spectroscopy. The adsorption experiments were carried out in a batch mode. The effect of initial AO7 concentrations (5-1000 mg/L), initial CPBr concentrations and pH of AO7 solution (2-9) on the adsorption capacity of SB and SBC were investigated. The experimental adsorption data were analyzed using Langmuir and Freundlich isotherm models. The adsorption of AO7 onto SB and SBC followed Freundlich and Langmuir isotherm models, respectively. The maximum uptake of AO7 was obtained by SBC4.0 (SB treated with 4.0 mMCPBr) with the adsorption capacity of 144.928 mg/g. The highest AO7 removal was found to be at pH 2 and 7 for SB and SBC, respectively. As a conclusion, sugarcane bagasse modified with CPBr can become an alternative adsorbent for the removal of anionic compounds in aqueous solution.